Enhancing biocompatibility and bone neoformation with nanostructured calcium aluminate cement - dos Santos, Andrea Fernanda Lopes; Vieira, Paula Fonseca Antunes; de Araújo, Juliani Caroline Ribeiro [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Castilho, Maiara Lima; de Oliveira, Ivone Regina; Raniero, Leandro (Springer Nature, 2023)
Purpose: Because of bone loss, bone complex fractures require medical intervention. Bone grafting may result in a positive recovery from bone loss. As a result, attempts are being made to investigate new bone grafting materials as alternatives, as well as to reproduce bone specificities on a wide scale. Because of its characteristics, Homogeneous Calcium Aluminate Cement (CACH) is a viable candidate for bone substitution. Gold (AuNPs) and silver (AgNPs) nanoparticles can improve CACH efficiency. The biocompatibility of CACH material linked with AuNPs and AgNPs was examined in vitro and in vivo in this study. Methods: SEM and mitochondrial activity percentage fluctuation were used to analyze materials in vitro for cell adhesion, proliferation, and biocompatibility. Meanwhile, histological examination of samples in vivo searched for bone neoformation. Results: SEM and mitochondrial activity percentage variation revealed efficient cell adhesion and proliferation when linking biocompatible material. In both samples, histological investigation revealed bone neoformation. CACH linked with AuNPs, on the other hand, produced the most relevant results. Conclusion: Although both samples showed bone neoformation, CACH combined with AuNPs generated a potentially efficient bone repair material as an enhanced bone substitute.
Keywords: Bone repair; Calcium aluminate cement; Nanoparticles